Power electronics and control techniques for maximum energy harvesting in photovoltaic systems - Femia, Nicola (Industrial electronics series., 2013)
"Preface Photovoltaic (PV) systems are nowadays producing a significant amount of the electrical energy used all around the world. The support the PV technology can offer in the next decades, to the rate of growth of the advanced economies as well as of the developing Countries, is very high. The incentives provided at a first stage by the European governments have resulted in the rapid growth of the photovoltaic market and in the increase of the number and quality of products offered by the industries. PV modules by many producers are nowadays commercially available and a number of power electronic systems have been put on the Market for processing the electric power produced by PV systems, especially for grid connected applications. Also the scientific literature concerning PV applications has been characterized by a strong quantitative and qualitative growth in the last decade. A huge number of papers has been written and continues to be published in many journals; moreover, high impact factor scientific journals which are specifically devoted to photovoltaic systems are printed. A significant number of scientific papers is dedicated to the control of the photovoltaic source. A simple search on the Reuters Thomson website reveals that, at the end of May 2012, about 600 papers include the Maximum Power Point Tracking among their keywords. Many authors have contributed to the scientific field of the circuits and systems ensuring the best operation of the photovoltaic generator, but a reference in this field is still lacking. Some books that try to assess the most significant improvements concerning the connection of the photovoltaic systems to the grid have been recently published"--